Injuries in artistic gymnastic elite adolescent male and female athletes - Kirialanis, P.; Malliou, P.; Beneka, A.; Gourgoulis, V.; Giofstidou, A.; Godolias, G. (Journal of Back and Musculoskeletal Rehabilitation, 2000)
Objectives: The purpose of this study was to record the incidence of Sport Injuries (acute and overuse syndromes) in Greek artistic gymnasts in relation to sex, age, event and exercise phase.